135k views
3 votes
Combine like terms to simplify the following expressions

-5a - 4a + b

2 Answers

0 votes

Answer:

= -9a+b

Explanation:

-5a+-4a =b

(-5a+-4a)+(b)

User MarkusParker
by
6.1k points
2 votes

Answer:

-9a + b

Explanation:

For this problem, let us factor out the variable a from the terms containing the variable, and apply addition and the distributive property to simplify the terms.

-5a - 4a + b

= a ( -5 + -4 ) + b

= a ( -9 ) + b

= -9a + b

Hence, the simplified expression for -5a - 4a + b is -9a + b.

Cheers.

User Honor
by
5.8k points